Medication Adherence and Perceptions of Pharmaceutical Care among Patients with Chronic Diseases in Tripoli, Libya - Beshna, Ebtesam; Shamsdoha Aboushagur; Alsbani, Abrar Khalifa (AlQalam Journal of Medical and Applied Sciences, 2026)
Abstract Medication adherence is crucial for effective chronic disease management, yet non-adherence remains a significant global challenge. Pharmaceutical care, including patient education and counseling, is a pivotal strategy to enhance adherence. This study aimed to assess medication adherence patterns and patient perceptions of pharmaceutical care among patients with chronic diseases in Tripoli, Libya. A descriptive, cross-sectional study was conducted between October and December 2025 in Tripoli, Libya. A convenience sample of 200 adult patients diagnosed with one or more chronic diseases for a minimum of six months was recruited. Data were collected using a structured, pretested questionnaire covering demographic and clinical characteristics, medication adherence behaviors, and patient perceptions regarding the pharmacist’s role. The study population exhibited a high prevalence of comorbidities, with 50% of participants having diabetes and 40% having hypertension. Adherence assessment revealed that 40% of patients reported sometimes or often forget to take their medication. A critical finding was the high rate of intentional non-adherence, with 70% of participants reporting they stop their medication if they experience side effects. Regarding pharmaceutical care, a significant majority of patients (85%) believed that the pharmacist’s counseling helps them adhere to their treatment, and 80% expressed a desire to receive more information or counseling from their pharmacist. While patients in Tripoli highly value the role of the pharmacist, the high rate of non-adherence linked to side effects represents a major, addressable barrier to optimal care. The findings underscore the urgent need for health authorities and pharmacists to implement standardized, proactive follow-up protocols focused on monitoring and managing adverse drug reactions. Leveraging the strong patient demand for counseling will be essential to fully integrate pharmacists into the chronic disease management team and significantly improve adherence rates in the region. Keywords. Medication Adherence, Pharmaceutical Care, Chronic Diseases, Pharmacist, Patient Perception, Tripoli, Libya.